PENGUKURAN KINERJA IMPLEMENTASI KEBIJAKAN PENANGGULANGAN KEMISKINAN STUDI KASUS: IMPLEMENTASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PARIWISATA DI DESA WISATA BRAYUT - , Nisa Agistiani R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is about performance measurement of public policy implementation. In this research, researcher takes a case study of implementation of PNPM Mandiri Pariwisata. The locus on this research is Desa Wisata Brayut, Kabupaten Sleman. PNPM Mandiri Pariwisata was implemented in Desa Wisata Brayut in 2009, 2010, and 2011. The purpose of this research is to determine the performance of the implementation of PNPM Mandiri Pariwisata in Desa Wisata Brayut. This research also aims to determine the factors that affect the performance of the implementation of PNPM Mandiri Pariwisata in Desa Wisata Brayut. To measure the performance of this particular program, researcher used two indicators. First, the policy output indicator (coverage, bias, access, and the synergy of program and target group needs). Second, the policy outcomes indicator (initial outcome, intermediate outcome, and long-term outcome).The method used in this research is qualitative method, which was performed by using two types of data: primary data and secondary data. The data and information in this research was obtained by in-depth interview, observation, and documents review. Validity of the data is tested using the triangulation technique, and the data itself is analyzed using the inductive data analysis technique. The results of this research indicate that implementation of PNPM Mandiri Pariwisata in Desa Wisata Brayut have a low performance. By âlow performanceâ, researcher means that this program has failed to achieve a longterm outcome, which is to improve the welfare of people in povertyin Desa Wisata Brayut. The results also indicate some factors that affect the low performance of implementation of PNPM Mandiri Pariwisata in Desa Wisata Brayut. These factors are the disposition of implementors and public policy format. Researcher made some policy recommendations based on those two factors: (1) modify the policy, (2) modify the form of policy/program, (3) make the details of monitoring and evaluation method, and (4) make the details of âpunishmentâ point in the PTO.